Utilization of Waste Plastic In Concrete - A Review - Nishant Kumar; Ajay Swarup (International Journal of Scientific Research in Civil Engineering, 2021)
Iraq industrial activities related to huge amounts of solid, non-biodegradable waste, waste low density Polyethylene (LDPE) plastic being among the well-known. So in this study, the scarped LDPE food boxes were transformed into fine particles and used as a sand for cement mortar and concrete. LDPE wastes were utilized to alter 0 to 25% of fine aggregates in mortar mixtures and 0% to 30% in concrete mixes at an increment of 5%. Compressive strength and dry density were tested for all mortar and concrete specimens. In addition, splitting tensile strength and ultrasonic pulse speed were tested for specimens of concrete. Results show that mass, pulse speed of ultrasonic, splitting and compressive tensile strengths were lowered as the size of LDPE raised. The lowest value of dry density, compressive strength and splitting strength was 2240 kg/m3, 18.7 MPa and 1.68 MPa, respectively, for 15% replacement of sand by the LDPE waste in concrete specimens. Whilst, the value of ultrasonic pulse velocity of LDPE concrete mixtures tends to decline lower than the reference values, but it remains nearly to the stander concrete mixtures and can be classified as excellent quality concrete. The density and compressive strength were decreased by using LDPE waste in mortar mixes for all replacement ratios reaching 12% and 42% respectively for 25% substitute. The use of plastic is increasing day by day, although steps were taken to reduce its consumption. This creates substantial garbage every day which is much unhealthy. A healthy and sustainable reuse of plastics offers a host of advantages.